Public art as research in the open: Thoughts on Alfredo Jaar’s Studies on Happiness as situational knowledge production - Hohlfeldt, Marion (Nordic Journal of Art & Research, 2021)
In 1979, the Chilean artist Alfredo Jaar staged his first public intervention in the context of military dictatorship. His inquiry on states of happiness anticipated a working method that Jaar has been following since. In taking Studies on Happiness as an early example of social aesthetics, this article will show that the work itself is not only seen as the product of making (poïesis), but that the process itself is seen as the embodiment of knowledge, the dwelling and outcome of an intended action. However, this action is not simply an act in the everyday (praxis), but as an intended action it is intelligent in itself and calls for the practical wisdom of acting (phronesis). As soon as the project includes a relational process and forms of participation, both in nature of unforeseeable outcome, the aim is no longer the production of a (common) object; rather, it is the social relation itself, established through the aesthetic or “boundary” object that puts into action the relation as well as the reflection on the conditions of its becoming. We will assess how play and phronesis can mediate between research and art by creating a situational knowledge, that is both critique and contributory: a research in the open.